Public speaking : connecting you and your audience - Andrews, Patricia; Andrews, James; Williams, Glen. (Boston : Houghton Mifflin, 1999)
This book is divided into five sections: Introducing Public Speaking; Knowing Yourself and Your Audience; Preparing the Speech; Presenting the Speech; and Informing, Persuading, and Inspiring.
Keywords: Public speaking; Public speaking -- Handbooks, manuals, etc